2016
DOI: 10.1007/s10072-016-2597-7
|View full text |Cite
|
Sign up to set email alerts
|

An SNP site in pri-miR-124, a brain expressed miRNA gene, no contribution to mesial temporal lobe epilepsy in an Italian sample

Abstract: Mesial temporal lobe epilepsy (MTLE) is the most common type of refractory epilepsy and is usually associated with hippocampal sclerosis (Hs). The pathogenesis of MTLE involves many biological pathways, some of which seem to be regulated by microRNAs (miRNAs). Increasing evidence shows that single nucleotide polymorphisms (SNPs) or mutations in miRNAs sequence may affect the processing and function of miRNAs and participate in the occurrence of diseases. In this study, the effect of the SNP of one neuronal miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…LncRNAs not only stimulate or inhibit the expression of target genes by combining directly with the target gene, but also participate in the regulation of gene expression by participating in histone modification as well as the recruitment of transcription factors . In addition, lncRNAs can also be used as ceRNAs that are capable of interacting with miRNAs, which together participate in the expression of target genes, and play significant roles in the occurrence and development of various diseases . LncRNAs are involved in the expression regulation of certain important coding genes, helping to facilitate nervous system growth and development in a certain space and in a certain time sequence, in addition to participating in the functioning of the nervous system .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs not only stimulate or inhibit the expression of target genes by combining directly with the target gene, but also participate in the regulation of gene expression by participating in histone modification as well as the recruitment of transcription factors . In addition, lncRNAs can also be used as ceRNAs that are capable of interacting with miRNAs, which together participate in the expression of target genes, and play significant roles in the occurrence and development of various diseases . LncRNAs are involved in the expression regulation of certain important coding genes, helping to facilitate nervous system growth and development in a certain space and in a certain time sequence, in addition to participating in the functioning of the nervous system .…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition, lncRNAs can also be used as ceRNAs that are capable of interacting with miRNAs, which together participate in the expression of target genes, and play significant roles in the occurrence and development of various diseases. 21 LncRNAs are involved in the expression regulation of certain important coding genes, helping to facilitate nervous system growth and development in a certain space and in a certain time sequence, in addition to participating in the functioning of the nervous system. 22 Recent studies have shown that specific lncRNA is closely related to neural cell differentiation, synapses, elevated neuronal excitability, and neural network connection and remodeling, suggesting that it may be involved in the occurrence and development of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In some previous studies, it has also been reported that rs531564 was not associated with impulsiveness, 13 mesial temporal lobe epilepsy, or Alzheimer’s disease. 12 , 23 However, because of the limitation of sample size, false-negative results may occur, especially for the correlation between rs531564 and antidepressant response. Thus, these findings need to be validated in a larger sample.…”
Section: Discussionmentioning
confidence: 99%
“…A number of candidate gene association studies have now been reported but there is no compelling evidence yet that genetic epilepsies are caused by mutations or variation in miRNA genes. [52][53][54][55] There has been no systematic effort to examine the contribution of miRNA sequence variation to human epilepsy. This is about to change.…”
Section: Genetic Variation In Mirnasmentioning
confidence: 99%